2014
DOI: 10.1371/journal.pone.0099002
|View full text |Cite
|
Sign up to set email alerts
|

Dose and Time-Dependent Selective Neurotoxicity Induced by Mephedrone in Mice

Abstract: Mephedrone is a drug of abuse marketed as ‘bath salts". There are discrepancies concerning its long-term effects. We have investigated the neurotoxicity of mephedrone in mice following different exposition schedules. Schedule 1: four doses of 50 mg/kg. Schedule 2: four doses of 25 mg/kg. Schedule 3: three daily doses of 25 mg/kg, for two consecutive days. All schedules induced, in some animals, an aggressive behavior and hyperthermia as well as a decrease in weight gain. Mephedrone (schedule 1) induced dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 57 publications
1
56
0
1
Order By: Relevance
“…To this end, the bath salt MEPH can be particularly useful in studying METH toxicity. Although DA depletion when MEPH is given at elevated ambient temperatures has been reported, as well as a potentially toxic in vitro effect (den Hollander et al, 2014;Martínez-Clemente et al, 2014), numerous studies conducted in this laboratory and others under ambient conditions known to produce METH toxicity have reported no significant longterm in vivo dopaminergic neurotoxicity when MEPH is administered in a binge regimen (Angoa-Pérez et al, 2012Baumann et al, 2012;den Hollander et al, 2013;Motbey et al, 2013;Anneken et al, 2015). As shown in Fig.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…To this end, the bath salt MEPH can be particularly useful in studying METH toxicity. Although DA depletion when MEPH is given at elevated ambient temperatures has been reported, as well as a potentially toxic in vitro effect (den Hollander et al, 2014;Martínez-Clemente et al, 2014), numerous studies conducted in this laboratory and others under ambient conditions known to produce METH toxicity have reported no significant longterm in vivo dopaminergic neurotoxicity when MEPH is administered in a binge regimen (Angoa-Pérez et al, 2012Baumann et al, 2012;den Hollander et al, 2013;Motbey et al, 2013;Anneken et al, 2015). As shown in Fig.…”
mentioning
confidence: 90%
“…The synthetic cathinones found in bath salts are less apt to produce lasting neurotoxicity compared with 3,4-methylenedioxymethamphetmine (MDMA) and methamphetamine (METH) (Angoa-Pérez et al, 2012;Baumann et al, 2012;den Hollander et al, 2013;Motbey et al, 2013;Anneken et al, 2015). This is despite a striking similarity in acute neurochemical and behavioral effects, including the aforementioned monoamine release, thermoregulation (Baumann et al, 2012;Fantegrossi et al, 2013;López-Arnau et al, 2014;Martínez-Clemente et al, 2014;Aarde et al, 2015;Kiyatkin et al, 2015;Shortall et al, 2016), hyperlocomotion (Baumann et al, 2012;López-Arnau et al, 2012;Marusich et al, 2012;Motbey et al, 2012;Wright et al, 2012;Aarde et al, 2013Aarde et al, , 2015Fantegrossi et al, 2013;Gatch et al, 2013), and measures of abuse potential (Hadlock et al, 2011;Lisek et al, 2012;Watterson et al, 2012;Aarde et al, 2013;Motbey et al, 2013;Karlsson et al, 2014).…”
mentioning
confidence: 99%
“…With regard to mephedrone, in vivo studies reported that there were no signs of striatal [17] or cortical [25] astroglial activation after administration of mephedrone in a binge paradigm. Similarly, no signs of microglial activation were observed in the striatum at 2 or 7 days after administration of mephedrone [17].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…In these animals, no increase in the density of [ 3 H]PK11195 binding sites was detected, indicating a lack of microglial activation [20]. However, Martinez-Clemente reported an increase in reactive astrocytes in the dentate gyrus of the hippocampus of mice treated with mephedrone at 7 days after a binge of 3 doses of 25 mg/kg for 2 days [25]. …”
Section: Neuroinflammationmentioning
confidence: 99%
“…Stimulant drugs, which have been approved for weight loss, include methamphetamine, fenfluramine, diethylpropion and bupropion (amfebutamone) (Weintraub et al, 1984;Bray, 1993). Of the legal highs thus far examined, a number have been shown to evoked weight loss in rodents (Martínez-Clemente et al, 2014). User reports from mephedrone abusers also suggest that this drug is anorectic as is methiopropamine (Winstock et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%